Description of two new species of Pseudochrominae from northern Palawan and Mindoro, Philippine Islands (Teleostei: Perciformes: Pseudochromidae) - Gill, Anthony C.; Williams, Jeffrey T. (Zootaxa, 2011)
Pseudochromis fuligifinis is described from 12 specimens from Verde Island, west coast of Mindoro and Apo Reef in the Philippines. It closely resembles P. elongatus Lubbock from Indonesia and P. striatus Gill, Shao & Chen from the Batanes Islands, Taiwan and the Ryukyu Islands, but differs in various meristic and coloration details. Manonichthys scintilla is described from five specimens from Coron Island and Apo Reef. It differs from congeners in fin shape and live coloration details.